Explore space using swarms of tiny satellites. (11th October 2018) - Levchenko, Igor; Keidar, Michael; Cantrell, Jim; Wu, Yue-Liang; Kuninaka, Hitoshi; Bazaka, Kateryna; Xu, Shuyan
Sand-grain-sized computers, self-healing materials and constellations of craft would reboot our reach, explain Igor Levchenko, Michael Keidar and colleagues. Sand-grain-sized computers, self-healing materials and constellations of craft would reboot our reach.